Lifeworld of Healthcare Professionals During the COVID-19 Pandemic in Northern Mindanao, Philippines - Buntod, April Rose; Ponce, Sulpecia (Journal of Interdisciplinary Perspectives, 2024)
Healthcare professionals are pivotal in maintaining human health and providing empathetic care based on scientific evidence. While extensive research has focused on the quantitative effects of COVID-19 on their well-being, there remains much to explore from a sociological perspective. This study posed an overarching question: How did the healthcare professionals in Mindanao navigate their lifeworld during the pandemic? Grounding on Habermas' colonization of the lifeworld, this study specifically aims to contribute to the discourse on the construction of self-care, family relationships, friendship relationships, and the perceived influences of the pandemic on these relationships. Using purposive and snowball sampling, this phenomenological study collected extensive data from August 2023 to April 2024 through in-depth interviews with nine healthcare professionals, comprising physicians (3), nurses (3), and medical technologists (3), all affiliated with three government-run hospitals in Northern Mindanao and had extensive experience managing COVID-19 patients. Based on the thematic analysis, interlocutors' self-care construction is associated with obtaining enough sleep and rest, relaxing, and taking breaks to unwind. COVID-19 also had significant implications for family dynamics, as it became a family affair. While the pandemic has negatively impacted family relationships, it has brought family members closer through constant yet indirect communication. In contrast, the pandemic strained the bonds between the interlocutors and their closest friends. The study concludes that a health disaster, COVID-19, has been found to restrict the interlocutors' lifeworld by limiting self-care practices and threatening social integration, making it difficult for them to return to their everyday routines.